2016
DOI: 10.1002/cb.1632
|View full text |Cite
|
Sign up to set email alerts
|

Consumer segments in social commerce: A latent class approach

Abstract: Social commerce is thriving; therefore, it becomes essential to recognize different types of social commerce shopper. In this study, we assume that social networking sites such as Facebook contain differently behaving consumer segments. Based on the assumption that the majority of social commerce shoppers are young adults, we are interested in identifying unobservable shopper segments that the young group may contain. A conceptual model has been tested that incorporates the psychological factor (trust), the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 74 publications
0
16
1
1
Order By: Relevance
“…The Internet in general is often seen as an environment for unethical behavior (Freeston and Mitchell 2004;Hajli 2018). For instance, e-commerce platforms (Bart et al 2005), social commerce platforms (Nadeem et al 2017), and SEPs (Sutherland and Jarrahi 2018) are all technology mediated platforms and the ethical concerns of consumers are highly common on these platforms. Sharing personal information online makes consumers vulnerable to both accidental and intentional harm by other consumers (Dinev and Hart 2006;Malhotra et al 2004).…”
Section: Consumers' Ethical Perceptions Of Sepsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Internet in general is often seen as an environment for unethical behavior (Freeston and Mitchell 2004;Hajli 2018). For instance, e-commerce platforms (Bart et al 2005), social commerce platforms (Nadeem et al 2017), and SEPs (Sutherland and Jarrahi 2018) are all technology mediated platforms and the ethical concerns of consumers are highly common on these platforms. Sharing personal information online makes consumers vulnerable to both accidental and intentional harm by other consumers (Dinev and Hart 2006;Malhotra et al 2004).…”
Section: Consumers' Ethical Perceptions Of Sepsmentioning
confidence: 99%
“…Although non-deception has been revealed as an essential part of consumers' ethical perceptions in other online contexts, our results revealed that it was non-significant in SEP. As the use of SEPs is constantly increasing (Zervas et al 2017) and thus the possibilities for data breaches and deception (Laczniak and Murphy 2019; Newcomer 2017; TheGuardian 2018) may also increase, consumer perceptions of non-deception may change very quickly. Further examination of the role of non-deception could include replicating the current study in the near future, or focus on examining whether consumer perceptions differ for different unobservable groups of respondents, i.e., latent classes (see, e.g., Nadeem et al 2017).…”
Section: Limitations and Further Research Directionsmentioning
confidence: 99%
“…We also validate and revise three salient characteristics of the social commerce environment from previous studies in the Facebook commerce context. The specific focus on Facebook commerce is a critical contribution that adds weight to literature on Facebook marketing (Nadeem et al, 2017). Our findings have identified the effects of two salient characteristics of social commerce platform (e.g., socialization, personalization) on brand engagement.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 72%
“…The target respondent is Generation Y, aged 18 to 35 years old, who uses social networks on a regular basis, and Facebook, in particular (Nadeem et al, 2017). This age cohort represents individuals who exhibited the largest level of Facebook usage in Vietnam in 2018 (Hootsuite, 2018).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation